Analysis of Preventive Maintenance on Heavy Dump Suspension Using Reliability-Centered Maintenance Method - Puspa, Sofia Debi; Tono Sukarnoto; Dany Nugraha Tantra; Christina Eni Pujiastuti; Joseph Andrew Leo (Jurnal Teknik, 2025)
The suspension system on Heavy Dump (HD) vehicles is crucial in maintaining stability, comfort, and reliability when used in harsh environments. HD vehicles have a hydraulic-pneumatic suspension that uses nitrogen gas and oil to overcome the load and vibrations from the road. The suspension maintains vehicle components and protects the load, especially when crossing damaged or bumpy roads at high speed. This study aims to optimize preventive maintenance planning using the Reliability-Centered Maintenance (RCM) method and determine the suspension system's preventive activities to reduce breakdowns. In designing effective preventive maintenance, the RCM approach and related methods, such as FMEA, are used to identify critical machines as the focus of analysis. In addition, a statistical distribution approach is used to determine the optimal maintenance activity interval. Based on the analysis results, it was obtained that the data follows a lognormal distribution where the optimization of preventive maintenance on the suspension component is every 370-hour time interval for each machine working. Changing the time interval increased the reliability value from 34.09% to 93.60% before and after preventive maintenance. Preventive maintenance activities with a time interval of 370 hours to reduce unscheduled breakdowns in the form of adjusting suspension components